Youth's Experiences of LGBTQ+-Inclusive Curriculum in a Secondary U.S. Classroom at the Intersections of Sexuality, Gender, Race, and Class. Issue 1 (3rd April 2023) - Schey, Ryan
ABSTRACT: Previous scholarship about LGBTQ+ inclusive curriculum has tended to focus on teachers' perspectives and drawn on binaries such as presence/absence. Extending past research, this article describes the experiences of youth, primarily but not exclusively LGBTQ+ youth, with LGBTQ+ inclusive curriculum with respect to intersecting identities and power relations, specifically, sexuality, gender, race, and class. Drawing from a yearlong ethnography at a public, comprehensive high school in a Midwestern U.S. city, I focus on one literacy learning context, a cotaught sophomore humanities course combining English and social studies. Taking up intersectionality's epistemological, ontological, and ethicopolitical commitments, the findings describe three sets of intersecting social dynamics that mattered for youth's classroom experiences and ultimately the liberatory (im)possibilities of LGBTQ+ inclusive curriculum: (1) queerness, disclosure, and agency; (2) social capital, class, and race; and (3) homonormativity, race, and outness. These findings offer implications for understanding the relations between LGBTQ+ inclusive curriculum and classroom and school climate.